Knowing nothing, staying stupid : elements for a psychoanalytic epistemology - Nobus, Dany (Routledge, 2005)
Why is stupidity sublime?What is the value of a 'dialectics of ignorance' for analysts and academics?Knowing Nothing, Staying Stupid draws on recent research to provide a thorough and illuminating evaluation of the status of knowledge and truth in psychoanalysis. Adopting a Lacanian framework, Dany Nobus and Malcolm Quinn question the basic assumption that knowledge is universally good and describe how psychoanalysis is in a position to place forms of knowledge in a dialectical relationship with non-knowledge, blindness, ignorance and stupidity. The book.